A1: Benefit Sharing Mechanisms to imrpove Water Productivity and Reduce Water-Related Conflict in Selected Basins - Estrada, R.D.; Escobar, G. (2009)
This project proposal deals with approaches to improving water usage in order to increase productivity and alternative water allocation and create conditions for designing and operating Benefit-Sharing Mechanisms.